Genetic and ecological consequences of interactions between three banksias in mediterranean-type shrubland - He, Tianhua; Lamont, Byron (Opulus Press, 2013)
Questions: Recent research has revealed that genotypic diversity may have a similar role to species diversity in understanding competitive relations and ecological functioning of a community. Despite theoretical advancement in how competition and co-existence influence the pattern of genetic diversity between interacting species/genotypes, this topic has received little empirical attention. The key question is how the distribution of a given species/genotype is influenced by inter-specific interactions. Location: A sclerophyll shrubland (kwongan) at Beekeepers Nature Reserve, 300 km north of Perth, Western Australia. Methods: We examined whether there are any genetic or ecological consequences arising from the interspersion of three Banksia species. We investigated patterns of local abundance, mortality after environmental stress (viz. severe drought) and microsatellite allelic richness for populations of the three co-occurring banksias distributed on the crests and slopes of a mosaic of sand dunes.Results: Local abundance of the fire-killed Banksia hookeriana was positively correlated with that of the lignotuberous resprouter B. attenuata, which has similar shrub morphology, but negatively with that of the less similar clonal resprouter, B. candolleana. In contrast, population allelic richness of B. attenuata and B. hookeriana were negatively correlated, while allelic richness of B. candolleana and the other two banksias were uncorrelated. Positive correlation between local abundance of B. attenuata and B. hookeriana was likely a consequence of a similar response to the same environmental resources, while B. candolleana has greater environmental tolerances than the other banksias but a slower dispersal rate as it rarely produces seedlings. Negative correlation in allelic richness between the ecologically similar B. attenuata and B. hookeriana was likely the result of competition for niche space at the genotype level. While local exclusion of inferior genotypes might occur by competition, exclusion of entire species is avoided and stable co-existence is achieved. Conclusions: Our results indicate that mechanisms of co-existence and isolation among plant species may operate at several genetic scales, and that subtle genotypic variation is of potential importance in maintaining co-existence among ecologically matched species.